Cerebral air embolism from a Central Venous Catheter: A timely reminder of the importance of rapid diagnosis. (16th August 2018) - Khaliq, Muhammad Farhan; Shoaib, Maria; Tariq, Syed Maaz; Khan, Muhammad Taimoor
Abstract : Cerebral air embolism (CAE) is a rare, avoidable and potentially fatal iatrogenic complication. Here, we report a case of CAE associated with a central venous catheter in the internal jugular vein that resulted in neurological deficits and generalised epileptic seizures. A 64-year-old man admitted for fasciotomy for compartment syndrome developed CAE with left-sided neurological deficits. The suspected origin was retrograde air flow from the right internal jugular venous catheter. The air spontaneously resorbed without the need for specific therapy, and he made a good recovery. CAE is an infrequent iatrogenic complication that requires prompt diagnosis to avoid significant morbidity and mortality. This case serves as a timely reminder that adverse outcome such as stroke, seizures or death can be avoided by a high index of suspicion and prompt diagnosis. Hyperbaric oxygen is the prime therapeutic measure, but high-quality evidence on its clinical value is lacking.